(3eWdY GdHOhQ heLeY GdHMhQs - (3CMeO Hf UGdM Hf CHj GdQLGd Gdjefj, Uaj GdOjf ,GHf nCHj GdpqQnLGd,J (B1092 (3g` s
(3ChdgG (B:s
(3UQa GdWGA Gdeged JQLeI GdWGgQ Hf jMji Hf GdMSf Hf LYaQ Hf YHO Gddg bGd ai GdBdi (B: (3cGf SjOkG aGVdkG s
(3BNQgG (B:s
(3bGd GHf YfHI (B: (3YGde cHjQ ef YdeGA GdRjOjI abjg eJcde Jhai HGdQi SfI SJ hYTQjf hKdGK eFI GfJgi GdLRA GdKGdK ef eWdY s
(3cJHJ Hbde eged GdfbW CMjGfkG hHYVg ajg HYV edGeM GdaGQSjIs
(3hJYGhQ YdjgG fGSNGfs
(3hWeSJ SfI GdfSN bUOkG s
(3hHChdgG JedcGJ CbOegG eDQN SfI (B1238 (3g` s
(3hagQS GdeJQLejf ddLRAjf GdKGdK gPG hGdQGHY s
(3hHgG fXGe GdJYbjHIs
Keywords: (3GdJGQjNs